[Translated article] Surgical treatment of ipsilateral bifocal tibial fractures: A challenge for the surgeon - A. Ortega-Yago; M. Barrés-Carsí; A. Balfagón-Ferrer (Revista Española de Cirugía Ortopédica y Traumatología)
Introduction: The association of ipsilateral tibia fractures has a low incidence, being up to 3.2% of total tibia fractures. Currently there is no gold standard regarding the ideal surgical treatment.The objective of this study is to analyze the surgical treatment and the radiographic and functional results, as well as the associated complication rate of ipsilateral bifocal tibia fractures. Material and methods: Retrospective observational study in our hospital from 2010 to 2022 of 24 patients who underwent bifocal fracture of the ipsilateral tibia. Demographic and surgical data and complications during follow-up were included. Results: The 24 patients were classified into Group 1 when they presented a fracture of the plateau and distal tibia (25%), Group 2 with a fracture of the plateau and diaphysis (33%) and Group 3 with a fracture of the diaphysis and distal tibia (42%). Three patients underwent surgery with 1 implant and 21 patients with 2 implants. The average follow-up time in outpatient clinics was 2 and a half years. At one year, 22 patients (92%) had full weight bearing and 2 patients had partial weight bearing (8%) due to the sequelae of the fractures. The average time for consolidation of the diaphysis was 7.75 ± 2 months, with no significant differences observed between Group 2 and Group 3 (p = 0.06). The average time for consolidation of the metaphysis was 3.50 ± 1.5 months, with no significant differences observed between Group 1 and Group 2 (p = 0.065). Seven patients (30%) had complications during follow-up. Conclusions: Bifocal tibia fractures can be treated using a combination of intramedullary nailing and plate osteosynthesis with good long-term results, obtaining an optimal union rate and low complications. In addition, it facilitates the reduction of the fracture, thus facilitating the patient's recovery and obtaining good long-term functional results. Resumen: Introducción: La asociación de fracturas ipsilaterales de tibia presenta una baja incidencia, siendo hasta el 3,2% de las fracturas totales de tibia. Actualmente no existe un patrón oro en cuanto al tratamiento quirúrgico idóneo.El objetivo de este estudio es analizar el tratamiento quirúrgico y los resultados radiográficos, funcionales, así como la tasa asociada de complicaciones de las fracturas bifocales de tibia ipsilaterales. Material y métodos: Estudio retrospectivo observacional de 24 pacientes intervenidos de fractura bifocal de tibia ipsilateral en nuestro hospital desde 2010 hasta 2022. Se incluyeron datos demográficos, quirúrgicos y complicaciones durante el seguimiento. Resultados: Los 24 pacientes se clasificaron en el grupo 1 cuando presentaban fractura de meseta y tibial distal (25%), en el grupo 2 con fractura de meseta y diáfisis (33%) y en el grupo 3 con fractura de diáfisis y tibia distal (42%). Tres pacientes fueron intervenidos mediante un implante y 21 pacientes mediante dos implantes. El tiempo medio de seguimiento en consultas externas fue de 2 años y medio; 22 pacientes (92%) presentaron al año carga completa y 2 pacientes, carga parcial (8%), debido a las secuelas de las fracturas. El tiempo medio de consolidación de la diáfisis fue de 7,75 ± 2 meses, sin observarse diferencias significativas entre el grupo 2 y el grupo 3 (p = 0,06). El tiempo medio de consolidación de la metáfisis fue de 3,50 ± 1,5 meses, sin observarse diferencias significativas entre el grupo 1 y el grupo 2 (p = 0,065); 7 pacientes (30%) tuvieron complicaciones durante el seguimiento. Conclusiones: Las fracturas bifocales de tibia son fracturas infrecuentes que en ocasiones requieren la combinación de varios tipos de osteosíntesis para obtener una reducción adecuada. En nuestra serie las fracturas más frecuentes fueron del tipo 3 (fractura de diáfisis y tibia distal). Cuando la diáfisis tibial estaba implicada se precisó de osteosíntesis combinada mediante clavo intramedular junto con placas y tornillos, obteniéndose unas tasas de consolidación, resultados funcionales a largo plazo y complicaciones similares a los descritos en la literatura.